"Effect of bacterial communication signals of DSF family on some virulence factors of bacterial angular spot Xanthomonas citri subsp. malvacearum on the cotton" (Damascus University Journal of agriculture sciences, 2024)
The bacteria, Xanthomonas spp depend on the Diffusible Signal Factor-family-DSF-family- to mediate their Quorum Sensing (QS) system, which controls the expression of the pathogenicity genes of the genus Xanthomonas, depending on the density of bacteria in the medium. Effect of different concentrations of DSF-family-containing extract of culture of the bactrial Xanthomonas citri subsp .malvacearum S101 (0.25, 0.5, 1.25, 7.5) mg\mL and (10, 50) µM of DSF pure signal on some virulence factors in Xcm S101 bacteria. The results showed that both DSF–family–containing extract of culture of Xcm S101 and DSF pure signal play a negative function on the ability of bacteria to express pathogenicity factors,  as the concentration of 0.25 mg/mL of the bacterial extract witch containing DSF-family and the concentration of 10 µM of DSF pure signal caused a reduction in bacterial growth Compared with the control logarithmically (1.8, 1.26) after 48 hours of incubation, while high concentrations (1.25, 7.5) mg/mL of bacterial extract- containing DSF-family and concentrations (50, 100) µM of DSF pure signal caused  the death of bacteria after (3,0;72,24)hours respectively. Incubation the bacterial extract containing DSF-family and DSF pure signal with concentrations (0.25 mg/mL, 10 µM), respectively, caused a decrease in the movement of bacteria in the medium by an average of (51, 78) % respectively compared to the control. while high concentrations of the bacterial extract or the pure DSF signal (0.5 mg/mL, 50 µM), respectively, caused inhibition of bacteria movement in the medium, and the bacterial extract reduced the production of EPS (0.25, 0.5, 1.25) respectively after 24 hours of incubation in NB medium. At a rate of (20.5, 38.6, 73.5) % respectively and production of proteases after d 48 hours of incubation at a rate of (33.4, 61, 100) %, as all extracts with concentrations (0.25, 0.5, 1.25) caused a reduction in biofilm formation at a rate of (31.6, 60, 70)% respectively, and its reduction when using the pure DSF signal at concentrations (10. 50) µM at a rate of (63.5, 68.9)% respectively.
Keywords: xcms101. QS; DSF.; protease; motility; exopolysaccaride; Biofilm